EVALUATION OF BACULOVIRUS PHTHORIMAEA VG IN LARVAE OF THE TUBER MOTH PHTHORIMAEA OPERCULELLA (ZELLER) - PÉREZ, LUZ E.; PUERTA, MARTHA C.; BUSTILLO, ALEX E.; MADRIGAL, ALEJANDRO (Revista Colombiana de Entomología, 1988)
Larva of Phthorimaea operculella (Zeller) was exposed to seven concentrations of a granulosis virus Baculovirus phthorimaea, which varied from 4,9 x 102 to 9,9 x 109 capsules/ ml. Concentrations were tested using a complete randomized design with four replications. In each replication 25 third-instar larvae (9 days-old at 21°C) were used. The virus was pathogenic to larvae of P. operculella, mortality varied from 39,2% to 98,7°/o for the lower and higher concentrations tested. The lethal medium time varied inversely with the concentration, this time was 5,2 days to the highest concentration and 16,2 days to the lowest concentration. The lethal medium concentration was 5,6 x 103 capsules/ml. There were no significant differences (P = 0,05) in virus susceptibility between the Antioquia and Cundinamarca insect populations.